Investing in sporting success as a domestic and foreign policy tool: the case of Qatar - Reiche, D. (International Journal of Sport Policy and Politics, 2014)
This article investigates why the small Middle Eastern country Qatar is investing so heavily in the sport sector. The country is hosting prestigious sporting events such as the Asian Games, the handball and the football World Cup, promotes elite sport success by local and naturalized athletes and invests in famous sport clubs abroad. The article analyses how sport is used as a domestic policy tool, for example to develop a healthy society and to attract white-collar expats from abroad. Sport is also used as a foreign policy tool to build relations with as many countries and people in the world as possible to gain soft power and for national security reasons.